Making the Euro area fit for the future - Ferdinand Fichtner; Marcel Fratzscher; Maximilian Podstawski; Dirk Ulbricht (DIW Economic Bulletin, 2014)
The crisis in the European currency area is not yet over. Although the situation in the financial markets is currently relatively calm, the economic crisis appears to be bottoming out in most countries. Nevertheless, there are still fundamental design flaws in the Monetary Union. If these are not fully addressed, it will only be a matter of time before a new crisis hits, and a partial or complete breakup of the Monetary Union cannot be ruled out. The economic consequences would be devastating, not least for Germany. To ensure the survival of the European Monetary Union, fundamental reform is required in three problem areas: the financial markets, public finances, and the real economy. In order to give the Monetary Union a stable foundation, all problem areas must be tackled equally; otherwise, due to interactions between these fields, success in one area might be canceled out by a flare-up of the crisis elsewhere. The present article outlines the elements of such a strategy for the institutional restructuring of the Monetary Union. Other articles in this and the next issue of DIW Economic Bulletin focus on the role of the ECB as the lender of last resort, the banking union and bank regulation, Community bonds, a European investment agenda, migration within the EU, a European unemployment insurance scheme, options for fiscal devaluation, and mechanisms for sovereign bankruptcies.
Keywords: E61; E44; H60; G18; 330; Euro crisis; Monetary union; Institutional reform; Banking crisis; Sovereign Debt crisis